First report of antibody response to SARS-CoV-2 mRNA vaccine in kidney transplant recipients - UNAGAMI, Kouhei; ISHIDA, Hideki; TAKAGI, Toshio; OMOTO, Kazuya; TANABE, Kazunari; FURUSAWA, Miyuki; YAGISAWA, Takafumi; ISHII, Kota; KANZAWA, Taichi; IIZUKA, Junpei (Japanese Journal of Transplantation, 2022)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), the virus that causes coronavirus disease (COVID-19), which was declared a pandemic in March 2020, has since caused a serious global health crisis. COVID-19 has spread to more than 200 countries and millions have fallen ill. Patients who have undergone an organ transplant are at increased risk of complications from COVID-19 due to conditions such as hypertension, diabetes, cardiovascular disease, chronic lung disease, and obesity, as well as chronic immunosuppression. We measured antibodies to the five SARS-CoV-2 proteins in kidney transplant patients who received two approved and available BNT162B2 (mRNA) vaccinations. It is possible to simultaneously identify antibody reactions to the extracellular domain (ECD), the three individual domains of the spike protein (S1, S2, and the receptor-binding domain (RBD)), and the five proteins of the nucleocapsid. The serological response following BNT162B2 COVID-19 mRNA vaccination was investigated using possible receptors. The subjects were 111 patients one month after receiving two coronavirus vaccines following kidney transplantation. Antibodies were found in 41% (46 cases). The positive rate of antibody formation tended to be low in transplant patients, whereas in the control group of healthy subjects it was 100%. The positive rate indicated by immunosuppressant was 36% (37/100) in the cases using tacrolimus at the time of vaccination and 90% (9/10) in the cases using cyclosporine. The intensity of each fragment in antibody-positive cases showed the normalized mean fluorescence intensity (nMFI), which indicated the highest ECD levels in the transplant patients and healthy control groups, followed by RBD, S1, and S2. In the reactivity pattern of the fragments of the positive cases, the control group had an nMFI of 110,000 to 140,000, while the transplant patients had an nMFI of 6,900 to 25,000, showing a difference in cumulative nMFI. The proportion of fragments also varied greatly among transplant patients, and no uniformity was observed. By contrast, in the healthy control group, the nMFI value tended to be constant for each fragment. The results suggest that performing antibody monitoring during the Coronavirus crisis may be useful for the protection against and treatment of infection as well as in determining the individual vaccination interval, vaccination amount, and number of vaccinations required.